Peran Guru PAUD dalam Menanamkan Kecintaan terhadap Bahasa Indonesia pada Anak Usia Dini - Febriana, Ika; Fitri, Cinta Atmaditia; Wardani, Dwie Nola; Nisa, Khoirun; Nasution, Nayla Amanda; Pasaribu, Nuraisyah; Tria, Reza Ade (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Indonesian is the state language which is the main means of communication in Indonesia. Instilling a love of this language in early childhood is very important to strengthen national identity. One of the parties who plays an important role in this matter is the Early Childhood Education (PAUD) teacher. PAUD teachers not only teach language skills, but also shape children's attitudes and interest in using Indonesian in everyday life. This article discusses the role of PAUD teachers in instilling a love of Indonesian in young children, as well as the strategies and challenges faced in this process. Through an approach based on related literature, this article aims to provide a clearer picture of the important role of PAUD teachers in Indonesian language learning.